Inequality and the 2019 Presidential Election in Indonesia: Beyond Identity Politics - Wahyu Prasetyawan (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
This study intends to understand vote based on economic evaluation at the 2019 presidential election in which Joko Widodo was incumbent, and Prabowo was the challenger. This paper argues that the presidential election in 2019 is a political arena where the voters assess the incumbent government’s economic policies, one of which is redistributive. Redistributive policies are understood as government policies intended to reduce the gap between the rich and poor people or inequality. This empirical study uses merged data from BPS, Bappenas, and the KPU. By employing a unique dataset, the originality of this study is located on the relevance of redistributive policies in political contestation. This study estimates the outcome of the presidential election using the ordinary least square (OLS) method. It points out that reducing inequality at the district level influenced the presidential election result. This paper stresses that the capability of the government to reduce inequality determines the result of the election.How to Cite:Prasetyawan, W. (2022). Inequality and the 2019 Presidential Election in Indonesia: Beyond Identitiy Politics. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 1-16. https://doi.org/10.15408/sjie.v11i1.22540.